LCA and Ecodesign Framework and Applications in the Electronics Sector - Christian Clemm; David Sánchez; Karsten Schischke; Nils F. Nissen; Klaus-Dieter Lang (Indonesian Life Cycle Assessment Network (ILCAN), 2019)
Life Cycle Assessment (LCA) is an indispensable tool in estimating the environmental impact of products and services. Generating estimates according to international standards is a crucial precondition towards optimizing the environmental performance of products and services. In Europe, the Ecodesign Directive (2009/125/EC) provides a method on how to determine impacts associated with energy-using and energy-related products, including electric and electronic equipment (EEE). One the one hand, efforts are being made to further harmonize LCA methods to allow for comparative assertions between different products and to eventually integrate LCA results into further parts of the European environmental legislation. On the other hand, LCA studies of electronics components, products, and product-service-systems can be very complex, reflecting the global supply chains, advanced production methods, and fast technological developments in the field of EEE. This paper provides and overview of both the LCA and Ecodesign framework, current developments in the field, and illustrates the intricacies of LCA studies in the field of EEE with a focus on consumer ICT and IT devices.